TRENDS IN ISLAMIC ECONOMICS AND SUSTAINABLE DEVELOPMENT GOALS (SDG’S) RESEARCH: A BIBLIOMETRIC ANALYSIS - Wiryawan, M. Ryzki; Isma, Resti Aprilia (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This study employs a literature review and bibliometric analysis to examine the connection between Islamic Economics and the SDGs. It seeks to systematically map the intellectual framework, knowledge growth trends, author contributions, the impact of sources, and the predominant topics. Data are gathered from the Scopus database and analyzed using R Studio and VOS Viewer. The aim of this study is to provide future researchers with an overview of the literature and its scope, while also helping them understand the development of research in this area and explore further topics related to it. Islamic Economics has the potential to contribute to resource mobilization efforts at the global, national, and local levels in achieving the SDGs. It plays a key role in promoting investment and trade to drive development and prosperity.